High-level roundtable on The impact of livestock research on sustainable development - International Livestock Research Institute (International Livestock Research Institute, 2021)
Held on on Wednesday 06 October 2021. Read about ILRI's impact book, covering over 45 years of research at:- ilri.org/ILRI-research-impact